Pre‐pregnancy body mass index, weight change during pregnancy, and risk of intellectual disability in children. Issue 3 (27th November 2012) - Mann, JR; McDermott, SW; Hardin, J; Pan, C; Zhang, Z
<x xml:space="preserve">Abstract</x> Objective This study investigated pre‐pregnancy body mass index (BMI) and weight change in pregnancy as potential risk factors for intellectual disability (ID) in children. Design Retrospective cohort study. Setting South Carolina, USA. Population A total of 78 675 mother–child pairs, insured by the South Carolina Medicaid programme, born in the period 2004–2007. Methods We analysed South Carolina Medicaid data, linked to data from both the South Carolina Department of Education (DOE) and the South Carolina Department of Disabilities and Special Needs (DDSN). Maternal pre‐pregnancy BMI and weight change during pregnancy were obtained from birth certificates. ID cases were identified from the three sources listed above. We used generalised estimating equation logistic regression models to model the odds of ID in children. Main outcome measures Identified as having ID in special education, DDSN, or Medicaid billing records. Results The risk of ID was greater in children of women with pre‐pregnancy obesity, and the risk was greatest in children born to women with morbid obesity (OR 1.52, 95% CI 1.30–1.77 for ID of any severity; OR 1.73, 95% CI 1.23–2.45 for severe ID). Gestational weight change (gain or loss) was not significantly associated with odds of ID. Conclusions Pre‐pregnancy obesity may be a modifiable risk factor for ID in children, although further study is needed to evaluate whether the association meets criteria for causation.